2008
DOI: 10.1021/np800226n
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Bulbophylol-B

Abstract: The first total synthesis of bulbophylol-B (1) has been achieved with the longest linear sequence of 12 steps and an overall yield of 17.9% via a new and practical approach to construct the dihydrodibenz[b,f]oxepin skeleton employing Wittig, selective reduction, and intramolecular Ullmann reactions as key steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 17 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…The key steps of the synthesis involve the coupling reaction of aromatic moieties 7 and 8 to construct the requisite carbon framework 9 ( 7 + 8 → 9 , Table 1), strategic salcomine oxidation of bisphenolic compound 11 to yield cyclization precursor 5 ( 11 → 5 , Scheme ), and formation of the seven‐membered dihydrooxepin ring (B ring) by ring closure of phenolic quinone 5 to complete the projected synthesis ( 5 → 4 , Table 2). Compared to other reported methods,57 the main advantages of the present synthesis are the higher yields and milder conditions. On the basis of this study, we are currently synthesizing additional analogues of 4 [e.g., possessing substituent group(s) on the benzene ring moiety] with the aim of exploring its structure–activity relationship.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The key steps of the synthesis involve the coupling reaction of aromatic moieties 7 and 8 to construct the requisite carbon framework 9 ( 7 + 8 → 9 , Table 1), strategic salcomine oxidation of bisphenolic compound 11 to yield cyclization precursor 5 ( 11 → 5 , Scheme ), and formation of the seven‐membered dihydrooxepin ring (B ring) by ring closure of phenolic quinone 5 to complete the projected synthesis ( 5 → 4 , Table 2). Compared to other reported methods,57 the main advantages of the present synthesis are the higher yields and milder conditions. On the basis of this study, we are currently synthesizing additional analogues of 4 [e.g., possessing substituent group(s) on the benzene ring moiety] with the aim of exploring its structure–activity relationship.…”
Section: Discussionmentioning
confidence: 84%
“…To date, the synthesis of naturally occurring dibenzo[ b , f ]oxepins has not been widely reported. In 2008, Yao and co‐workers reported the first total synthesis of bulbophyol B ( 3 ) by using an intramolecular Ullmann‐type biaryl ether formation reaction (18 % overall yield in 12 steps) 5. In the following year, Kraus and co‐workers reported the first total synthesis of bauhinoxepin J ( 4 ) by employing unique intramolecular radical cyclization of a quinone ring (25 % overall yield in 4 steps) 6.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported higher yields and shorter reaction times compared with conventional heating and sealed tubes. These macrocyclic diaryl ethers are commonly found in natural compounds ( Figure 12) and have been reported to mediate a broad range of biological activities [94][95][96]. The buflavine derivatives encompassing a 8-membered cycle 246, were obtained by allylation of biaryls 244 and subsequent RCM using Grubb's II catalyst.…”
Section: Mw-assisted Syntheses Of Macrocyclic Natural Products and Anmentioning
confidence: 99%
“…This natural product was synthesized by employing Wittig and Ullmann reactions as key steps. 247 The intramolecular C-O formation was performed by using 2 equiv. of copper catalyst to give the 7-membered ring product in 89% yield (Scheme 75).…”
Section: Introductionmentioning
confidence: 99%